2009
DOI: 10.1542/peds.2008-1003
|View full text |Cite
|
Sign up to set email alerts
|

Value of Imaging Studies After a First Febrile Urinary Tract Infection in Young Children: Data From Italian Renal Infection Study 1

Abstract: The benefit of performing ultrasonography and scintigraphy in the acute phase or cystourethrography is minimal. Our findings support (1) technetium-99m-dimercaptosuccinic acid scintigraphy 6 months after infection to detect scarring that may be related to long-term hypertension, proteinuria, and renal function impairment (although the degree of scarring was generally minor and did not impair renal function) and (2) continued surveillance to identify recurrent urinary tract infections that may warrant further i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
65
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(76 citation statements)
references
References 33 publications
4
65
0
7
Order By: Relevance
“…Many studies have similar limitations. 6,7,9,19,24 Other studies have limited generalizability owing to narrow 10,25 or broad [26][27][28] age ranges, or small sample size. 8,[26][27][28] One study looked specifically at the predictive value of ureteral dilation as an isolated finding on RBUS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have similar limitations. 6,7,9,19,24 Other studies have limited generalizability owing to narrow 10,25 or broad [26][27][28] age ranges, or small sample size. 8,[26][27][28] One study looked specifically at the predictive value of ureteral dilation as an isolated finding on RBUS.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of these papers have limitations that make it impossible to determine the test characteristics of RBUS; most common is that many studies do not provide sufficient data to directly compare RBUS findings with VCUG findings in individual patients. [12][13][14][15][16][17][18][19] Other studies focus on the value of RBUS to predict renal scintigraphic findings (scarring). 13,[20][21][22] Verification bias is a common weakness in the published literature.…”
mentioning
confidence: 99%
“…Montini et al analyzed data of 300 children with acute pyelonephiritis with USG evaluation and found that USG detected VUR only in 27.27%. The ability of USG to predict the renal parenchymal damage was also limited to only 26.66% and they were found to have parenchymal scarring by DMSA [8]. In our study, USG showed signs of pyelonephritis in 62(71.2%) children and cystitis in 25(28.8%).…”
Section: Discussionmentioning
confidence: 47%
“…The follow-up DMSA scan showed scarring in 28% of those with initial diagnosis of acute pyelonephritis. He concluded that DMSA should be done 6 months after infection to detect scarring that may be lead to hypertension and proteinuria [8]. In our center, DMSA in acute phase picked up acute pyelonephritis in 81.5% children, follow-up scan done between 6 months to 1 year revealed evidence of scars in 44(29.1%) children.…”
Section: Discussionmentioning
confidence: 72%
“…1 Like other studies of this topic, [2][3][4][5][6] this is a retrospective analysis of data captured through routine care, but it is probably the largest and most well-conducted study of its kind. Their findings are consistent with most earlier work, and their conclusions valid: RBUS is a lousy screen for vesicoureteral reflux (VUR).…”
mentioning
confidence: 99%